Beating Goliath : Why Insurgencies Win - Record, Jeffrey (Washington, D. C. Potomac Books, 2009)
Beating Goliath examines the phenomenon of victories by the weak over the strong-more specifically, insurgencies that succeeded against great powers. Jeffrey Record reviews eleven insurgent wars from 1775 to the present and determines why the seemingly weaker side won.
Include Index, Bibliography, Glossary and Notes
Keywords: Iraq -- Vietnam War (1961-1975) -- Iraq War (2003-2011)